Electromigration reliability study on copper interconnects under pulsed current conditions - Lim, Meng Keong (2015)
Although most interconnects carry pulsed current signals during field operations, most of our understanding on electromigration has been obtained from direct current (D.C.) studies. As continuous scaling has demanded interconnects to carry higher current density and achieve lower failure rate with each generation of technology node, there is a need to understand the behavior of electromigration under pulsed current conditions, since pulsed current is a less severe form of stress as compared to D.C. Simulations and experiments are conducted to study electromigration in copper interconnects under unipolar pulsed current stress. The time to nucleate a void is proportional to the inverse square of duty cycle, while the time taken to grow a void is inversely proportional to duty cycle. Cu interconnects that were subjected to unipolar pulsed current with long periods showed enhanced lifetime when the pulse on-time was shorter than the t50 of test lines that were subjected to D.C. stress conditions. We have proposed a model for predicting the lifetime of interconnects that are subjected to unipolar pulsed current stress condition. The lifetime prediction obtained from our proposed model was found to fit experimental data more accurately than those obtained from On-Time model or Average Current Density model. With the aid of simulation, interconnects that were subjected to unipolar pulsed current stress were found to be immortal when the product of the periodic average current density and length of interconnect is less than the critical product of D.C. current density and length of interconnect, i.e. (dj)pulseL < (jD.C.L)crit. The electromigration behavior of Cu interconnects under bipolar pulsed current stress conditions were also studied in this work. Experimental results showed that partial healing of void occurred in Cu interconnects even when symmetrical bipolar pulsed current stress was applied. The lifetime of Cu interconnects were found to depend on the direction of electron current flow during the first half-period. Cu interconnects showed enhanced electromigration lifetime when the half-period of bipolar pulsed current was shorter than the t50 of test lines that were subjected to D.C. stress. An analytical model was proposed to determine the immortality criterion for interconnects that are subjected to bipolar pulsed current stress. The model was validated using simulation technique and our results showed that the model can be applied in cases when the bipolar pulsed current has a frequency of 1 Hz or higher. The collective results from this work show that interconnects have longer electromigration lifetime under unipolar or bipolar pulsed current stress, as compared to D.C. stress. The design rules that are derived from accelerated D.C. test can be relaxed and yet provide sufficient reliability margin for interconnects that carry unipolar or bipolar pulsed current signals.